Do College Students Use Online Self-Help? A Survey of Intentions and Use of Mental Health Resources. Issue 3 (3rd July 2018) - Levin, Michael E.; Stocke, Krista; Pierce, Benjamin; Levin, Crissa
ABSTRACT: Online self-help may help increase the reach of mental health services for college students, but little research has examined students' actual interest/use of these resources. An online survey of 389 college students examined intentions and use of online mental health resources as compared with other support options. Findings indicated the highest intentions/use of informal supports (e.g., parents, friends) for mental health problems and lowest intentions/use for online self-help. However, a subset of students showed a preference for online self-help over other forms of support. Participants were also more likely to request online self-help resources (21%) than in-person therapy resources (9%) when offered these options. Reported barriers were also identified for using mobile applications (apps) specifically (e.g., stigma, credibility, privacy). Overall, results suggest mixed findings and relatively low interest for use of online self-help among college students, while highlighting potential barriers that might be addressed to increase engagement.